Microbiota-induced obesity requires farnesoid X receptor - Parséus, Ava (Gut, 2017)
OBJECTIVE: The gut microbiota has been implicated as an environmental factor that modulates obesity, and recent evidence suggests that microbiota-mediated changes in bile acid profiles and signalling through the bile acid nuclear receptor farnesoid X receptor (FXR) contribute to impaired host metabolism. Here we investigated if the gut microbiota modulates obesity and associated phenotypes through FXR. DESIGN: We fed germ-free (GF) and conventionally raised (CONV-R) wild-type and Fxr−/− mice a high-fat diet (HFD) for 10 weeks. We monitored weight gain and glucose metabolism and analysed the gut microbiota and bile acid composition, beta-cell mass, accumulation of macrophages in adipose tissue, liver steatosis, and expression of target genes in adipose tissue and liver. We also transferred the microbiota of wild-type and Fxr-deficient mice to GF wild-type mice. RESULTS: The gut microbiota promoted weight gain and hepatic steatosis in an FXR-dependent manner, and the bile acid profiles and composition of faecal microbiota differed between Fxr−/− and wild-type mice. The obese phenotype in colonised wild-type mice was associated with increased beta-cell mass, increased adipose inflammation, increased steatosis and expression of genes involved in lipid uptake. By transferring the caecal microbiota from HFD-fed Fxr−/− and wild-type mice into GF mice, we showed that the obesity phenotype was transferable. CONCLUSIONS: Our results indicate that the gut microbiota promotes diet-induced obesity and associated phenotypes through FXR, and that FXR may contribute to increased adiposity by altering the microbiota composition.